The effects of privatization and consolidation on bank productivity: comparative evidence from Italy and Germany - Elisabetta Fiorentino; Alessio De Vincenzo; Frank Heid; Alexander Karmann; Michael Koetter (Deutsche Bundesbank, 2009)
The Italian and German banking systems shared similar characteristics early in the 1990s but have evolved in different directions since then: Italy privatized its publicly-owned banks while Germany has maintained a large share of state-owned savings banks. Contemporaneously, banks in both markets engaged heavily in mergers and acquisitions. We analyze how these activities have affected banks' productivity in the period 1994-2004, differentiating between technical change, efficiency change and scale economies. We find that privatized banks experienced a significant increase in productivity, especially if they subsequently merged with other banks. German banks were still able to increase their productivity through consolidation.
Keywords: D24; G21; G28; L33; 330; Banking market integration; deregulation; total factor productivity; Italy; Germany; Bank; Produktivität; Öffentliche Bank; Privatisierung; Übernahme; Fusion; Deutschland; Italien